Analysis of the ability of minors in Spain to recognize commercial content published by influencers - Zozaya Durazo, Luisa Dolores (2022)
Minors are exposed to various contents when browsing the Internet, this study specifically explores those created by influencers, who stand out for sharing advertising in a hybrid format and represent a greater challenge to be identified as such. The objective of the research is to find out the criteria by which minors process information when they consume advertising content shared by influencers, paying special attention to those elements of the publication that arouse their questioning. To answer the questions raised, 12 discussion groups were held where 62 minors between 11 and 17 years of age from private, concerted and public schools in Spain participated during the first semester of 2021.The results show that in general minors identify a commercial link between brands and influencers, however, and especially with the youngest, they are not able to identify when paid content is presented to them, if it is not marked as such; For their part, adolescents have certain resources that activate their critical attitude towards influencer marketing: the profile of the influencer and their degree of affinity with the promoted product.